2020
DOI: 10.3390/plants9080994
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and Functional Screening of Three Species Traditionally used as Antidepressants: Valeriana officinalis L., Valeriana jatamansi Jones ex Roxb. and Nardostachys jatamansi (D.Don) DC.

Abstract: The essential oils (EOs) of three Caprifoliaceae species, the Eurasiatic Valeriana officinalis (Vo), the Himalayan Valeriana jatamansi (Vj) and Nardostachys jatamansi (Nj), are traditionally used to treat neurological disorders. Roots/rhizomes micromorphology, DNA barcoding and EOs phytochemical characterization were carried out, while biological effects on the nervous system were assessed by acetylcholinesterase (AChE) inhibitory activity and microelectrode arrays (MEA). Nj showed the highest inhibitory activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The white to pink inflorescences develop in the second year after vernalization. The rootstock forms a dense meshwork of thin roots [ 302 ], [ 13 ] (p.692), with a clonical, dull brown colored rhizome and many long strout attached roots [ 304 ]. While the fresh root is odorless, dried roots smell distinctly unpleasant, comparable with valeric acid and camphor [ 305 , 306 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
See 3 more Smart Citations
“…The white to pink inflorescences develop in the second year after vernalization. The rootstock forms a dense meshwork of thin roots [ 302 ], [ 13 ] (p.692), with a clonical, dull brown colored rhizome and many long strout attached roots [ 304 ]. While the fresh root is odorless, dried roots smell distinctly unpleasant, comparable with valeric acid and camphor [ 305 , 306 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Furthermore, >0.17% valerenic acids are requested [ 307 ]. Oxygenated monoterpenes, monoterpene hydrocarbons, oxygenated sesquiterpenes, and sesquiterpene hydrocarbons were registered as the most abundant constituents [ 304 , 315 ]. Several publications on valerian root oils clearly indicated remarkable compositional differences, according to various geographic origins.…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
See 2 more Smart Citations
“…These protective effects are due to the ability of V. officinalis and its main constituents such as valerenic acid and acetylvalerenolic acid, to inhibit the activity of the nuclear factor (NF)-κB in vitro [ 165 ]. Other studies showed that the CNS effects of V. officinalis, V. jatamansi, and N. jatamansi can certainly also attributed to the inhibitory activity exerted on AChE [ 166 ].…”
Section: Preclinical and Clinical Effectiveness In Humans And Patentsmentioning
confidence: 99%